2022
DOI: 10.1007/s00586-022-07307-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hybrid artificial intelligence in determining candidacy for lumbar stenosis surgery

Abstract: Purpose Lumbar spinal stenosis (LSS) is a condition affecting several hundreds of thousands of adults in the United States each year and is associated with significant economic burden. The current decision-making practice to determine surgical candidacy for LSS is often subjective and clinician specific. In this study, we hypothesize that the performance of artificial intelligence (AI) methods could prove comparable in terms of prediction accuracy to that of a panel of spine experts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In a previous article, Mourad et al found similar results for prediction error (AUROC and Cohen’s kappa were .9266 and .6298 respectively) using a hybrid AI model in determining candidates for lumbar surgery in LSS based on surgeon decisions on medical vignettes. 10 Similarly, another study showed similar prediction error (AUROC = .90) with a cohort of 387 patients. 11 Interestingly, Wilson et al obtained good predictions with ML on MRI imaging only, with AUROC = .88.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In a previous article, Mourad et al found similar results for prediction error (AUROC and Cohen’s kappa were .9266 and .6298 respectively) using a hybrid AI model in determining candidates for lumbar surgery in LSS based on surgeon decisions on medical vignettes. 10 Similarly, another study showed similar prediction error (AUROC = .90) with a cohort of 387 patients. 11 Interestingly, Wilson et al obtained good predictions with ML on MRI imaging only, with AUROC = .88.…”
Section: Discussionmentioning
confidence: 69%
“…7,8 Other ML approaches included surgery decision making to identify surgical candidates based on surgeon's recommendation 9 or predicting postoperative outcomes. 10,11 Here, we propose a novel ML approach to compute the recommendation probability of spinal surgery for LSS based on MD decision making instead of surgeon's recommendation. The model consists of a random forest model trained to accurately estimate model parameters from medical vignette data reviewed by MDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mourad et al created a hybrid AI model that evaluated clinical symptoms, MRI, and demographic factors to determine surgical candidacy for lumbar spinal surgery. Their model performed in a similar way to a multidisciplinary team, which included five fellowship-trained spine surgeons [45]. A separate retrospective study had 86% agreement in its surgical plan, with the actual treatment course using demographics, medical history, patient-reported outcome measures, and radiographic parameters as guidance [46].…”
Section: Artificial Intelligencementioning
confidence: 99%